If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = 11x + 8 Reorder the terms: 6 + 3x = 11x + 8 Reorder the terms: 6 + 3x = 8 + 11x Solving 6 + 3x = 8 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 6 + 3x + -11x = 8 + 11x + -11x Combine like terms: 3x + -11x = -8x 6 + -8x = 8 + 11x + -11x Combine like terms: 11x + -11x = 0 6 + -8x = 8 + 0 6 + -8x = 8 Add '-6' to each side of the equation. 6 + -6 + -8x = 8 + -6 Combine like terms: 6 + -6 = 0 0 + -8x = 8 + -6 -8x = 8 + -6 Combine like terms: 8 + -6 = 2 -8x = 2 Divide each side by '-8'. x = -0.25 Simplifying x = -0.25
| 23+x=49 | | 73-x=83-2x | | y=-4+260 | | 4x+6+4=1 | | 7x+1=24 | | 6m+m+4+6= | | 3x-33=2x+29 | | x+7+x+4+x+11=x+5+x | | 6b^3-28b^2+30b= | | 2=6+6-2x | | .13x+8=65+10x | | 2p-4=90 | | 15-6x-2y=4 | | 1/2(48=40)35 | | 42-(3c+4)=2(c+4)+6 | | 30+6y=12+6w | | -p+12=8 | | 1/2(48=40 | | 14=2(2n-1) | | 0.5x+12=46 | | .8s=24 | | 4x-11=x+55 | | 6-3+4x+1=1x+4 | | 57-x=41 | | .75e=15 | | 26=3y-17 | | 6-3+4x+1=1x+5 | | 10=2y-17 | | 3x+200=4x | | 19x+7y=-13 | | 10=2y-16 | | 1+7x=7x+1 |